The Urgency of Sufism and Self-Control in Millennial Juvenile Delinquency - Millatina Hanifah; Vateen Nayla Nurul Varyda (Da'wa Faculty of Islamic State University Salatiga, 2024)
Adolescence is when children and teenagers start to develop what they like; during this period, they also find it difficult to control their emotions. In the current millennial era, there are many character, manners, and moral shifts in every growth journey during adolescence. Thus, it is proven that there are still many confusing problems among teenagers today, such as brawls between one group and another, consuming drinks that Islam does not permit, and so on. This problem occurs because of the decline in morals and even the decline in moral and ethical values ​​that make teenagers lose their identity. The method used in this research is qualitative, with a descriptive approach supported by literature references from books, journals, and other sources. This research aims to determine the urgency of Sufism and self-control in millennial juvenile delinquency. The results found were that practicing Sufism correctly and appropriately can increase self-control of adolescent behavior and actions that are deviant and detrimental to themselves and others.